2016
DOI: 10.1111/hcre.12093
|View full text |Cite
|
Sign up to set email alerts
|

Overconfidence at the Keyboard: Confidence and Accuracy in Interpreting Affect in E-Mail Exchanges

Abstract: Although much research exists suggesting affect is effectively transmitted in computer-mediated communication (CMC), much of it focuses on how a writer encodes affect in a message or how a reader decodes affect in a message, rather than the communication process as a whole. For example, Lo (2008) created messages that either had an emoticon or did not. The author found that the presence of emoticons significantly changed the reader's perception of the writer's affect. Walther and D' Addario (2001), using the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 21 publications
4
28
1
Order By: Relevance
“…This converges with past findings showing that standard positive messages are equally likely to increase relationship satisfaction as customized ones (Luo & Tuney, 2015). Is seems that when several positive emotional cues are included in the same message they are perceived as redundant, rather than having an additive effect (for a discussion, see Riordan & Trichtinger, 2017). For negative replies, in contrast, additional cues do not seem to be redundant.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This converges with past findings showing that standard positive messages are equally likely to increase relationship satisfaction as customized ones (Luo & Tuney, 2015). Is seems that when several positive emotional cues are included in the same message they are perceived as redundant, rather than having an additive effect (for a discussion, see Riordan & Trichtinger, 2017). For negative replies, in contrast, additional cues do not seem to be redundant.…”
Section: Discussionsupporting
confidence: 88%
“…This being the case, no interaction should be observed (H3a). On the other hand, emotional cues may have a redundant, rather than an additive, effect on positive replies, because they express the same information and are perceived as lacking usefulness in such cases (Riordan & Trichtinger, 2017). Therefore, differences according to emotional cues could be less likely to occur for positive replies due to a ceiling effect.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were found in studies asking people to communicate an emotional message via e-mail to either a friend or a stranger ( Kruger et al, 2005 —Experiment 3; Riordan & Trichtinger, 2017 —Experiment 3). Although friends and strangers were equally accurate in detecting the emotional tone of a message, friends expected to be more accurate than strangers.…”
Section: Comparing Friends’ and Strangers’ Conversationssupporting
confidence: 82%
“…Many studies have shown that people who have a close bond (e.g., couples, good friends) have the feeling they understand each other especially well ( Kruger, Epley, Parker, & Ng, 2005 ; Pollmann & Finkenauer, 2009 ; Riordan & Trichtinger, 2017 ; Savitsky et al, 2011 ; Swann & Gill, 1997 ). For example, Savitsky et al (2011) gave their participants ambiguous phrases to communicate to either their spouse or to a stranger (e.g., “What have you been up to?” can convey not only interest in someone’s well-being but also irritation that someone is late) and found that spouses were no better in conveying the intended meaning of a sentence than strangers.…”
Section: Comparing Friends’ and Strangers’ Conversationsmentioning
confidence: 99%